2022
DOI: 10.1021/acsnano.2c04189
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Free Direct Optical Lithography of Bare Colloidal Nanocrystals via Photo-Oxidation of Surface Ions with Porosity Control

Abstract: Microscale patterning of colloidal nanocrystal (NC) films is important for their integration in devices. Here, we introduce the direct optical patterning of all-inorganic NCs without the use of additional photosensitive ligands or additives. We determined that photoexposure of ligand-stripped, “bare” NCs in air significantly reduces their solubility in polar solvents due to photo-oxidation of surface ions. Doses as low as 20 mJ/cm2 could be used; the only obvious criterion for material selection is that the NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…In direct optical lithography, patterns are formed by photoinduced chemical reactions of photosensitive ligands or additives, which result in a solubility change of nanomaterials [e.g., metal oxide (16), PeNCs (17), and QDs (12)] at light-exposed regions without the need for a polymeric photoresist. Various photosensitive motifs and photochemical reactions such as azide (17)(18)(19)(20)(21), benzophenone (22), cinnamoyl (23), photo-acid generation (12), oxime sulfonate (13), thiol-ene (24)(25)(26)(27), photo-amine generation (28), oxide bridging (16), photo-oxidation (29), and alkene cross-linking (30) have been explored for direct optical patterning of colloidal emissive nanocrystals. However, the lithography process often induces substantial surface damage to the deposited emissive nanomaterials, thereby degrading their optical properties such as PLQY (13,17).…”
Section: Introductionmentioning
confidence: 99%
“…In direct optical lithography, patterns are formed by photoinduced chemical reactions of photosensitive ligands or additives, which result in a solubility change of nanomaterials [e.g., metal oxide (16), PeNCs (17), and QDs (12)] at light-exposed regions without the need for a polymeric photoresist. Various photosensitive motifs and photochemical reactions such as azide (17)(18)(19)(20)(21), benzophenone (22), cinnamoyl (23), photo-acid generation (12), oxime sulfonate (13), thiol-ene (24)(25)(26)(27), photo-amine generation (28), oxide bridging (16), photo-oxidation (29), and alkene cross-linking (30) have been explored for direct optical patterning of colloidal emissive nanocrystals. However, the lithography process often induces substantial surface damage to the deposited emissive nanomaterials, thereby degrading their optical properties such as PLQY (13,17).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the protective NaYF 4 outer shell (Figure S1 shows elemental mapping of Gd 3+ and Y 3+ ions) was used to reduce surface quenching and prevent excitation energy spill-out from the Gd 3+ network. , As synthesized, the Eu 3+ -activated ANPs were observed to be a pure Na­(Y/Gd)­F 4 β-phase (Figure S2) and less than 25 nm in diameter, determined by powder X-ray diffraction (XRD) and transmission electron microscopy (TEM), respectively. High crystallinity, small size, and narrow size distribution (<5%) ideally position these ANPs for biological or nanoscale patterning applications. …”
mentioning
confidence: 99%
“…42 Recently, we also showed that bare, absorbing NCs such as ZnSe and ZnS NCs can be patterned directly without having to add any other photosensitive component. 41 After subjecting the films to a hot isostatic pressing (HIP), a refractive index of up to 2.22 (at 633 nm) was obtained which corresponded to a packing fraction of 0.87. On the other hand, the addition of block copolymer micelles enabled the fabrication of NC patterns with lower inorganic fractions and increased porosity, thus allowing patterning of low-k dielectric components valuable for high-frequency electronic components and antireflective coatings.…”
Section: Inorganic Fractionmentioning
confidence: 99%
“…Copyright 2021 American Chemical Society. (F) Adapted with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Figures Of Meritmentioning
confidence: 99%
See 1 more Smart Citation